Anti-obesity and anti-inflammatory effects of synthetic acetic acid vinegar and Nipa vinegar on high-fat-diet-induced obese mice - Beh, Boon Kee; Mohamad, Nurul Elyani; Swee, Keong Yeap; Huynh, Ky; Boo, Sook Yee; Yi, Joelle Heng Chua; Tan, Sheau Wei; Wan, Yong Ho; Sharifuddin, Shaiful Adzni; Long, Kamariah; Mohammed Alitheen, Noorjahan Banu (Nature Publishing Group, 2017)
Recently, food-based bioactive ingredients, such as vinegar, have been proposed as a potential solution to overcome the global obesity epidemic. Although acetic acid has been identified as the main component in vinegar that contributes to its anti-obesity effect, reports have shown that vinegar produced from different starting materials possess different degrees of bioactivity. This study was performed to compare the anti-obesity and anti-inflammatory effects of synthetic acetic acid vinegar and Nipa vinegar in mice fed a high-fat diet. In this work, mice were fed a high-fat diet for 33 weeks. At the start of week 24, obese mice were orally fed synthetic acetic acid vinegar or Nipa vinegar (0.08 and 2 ml/kg BW) until the end of week 33. Mice fed a standard pellet diet served as a control. Although both synthetic acetic acid vinegar and Nipa vinegar effectively reduced food intake and body weight, a high dose of Nipa vinegar more effectively reduced lipid deposition, improved the serum lipid profile, increased adipokine expression and suppressed inflammation in the obese mice. Thus, a high dose of Nipa vinegar may potentially alleviate obesity by altering the lipid metabolism, inflammation and gut microbe composition in high-fat-diet-induced obese mice.